Direksi Sebagai Penjamin Perorangan Dalam Hal Kepailitan Pada Perseroan Terbatas - Ranitya Ganindha (Universitas Widya Gama Malang, 2020)
The commitment of individual maintenance or personnel guaranntor often leads to rights removal of the personal guarantor so that an offense from the personal guarantor leads to bankruptcy. In some cases, for example in the case that happened to PT Hardy, the position of the personal guarantee which was initially intended as a guarantor that the debtor would pay off all his debts to the creditor, then his position could change to become like the main debtor who could be sued to be responsible for debt repayment without having to do confiscated in advance of the bankruptcy assets owned by the main debtor. The main problem to be examined is how the position of the board of directors who act as a personal guarantee issue in the bankruptcy of a limited company. The purpose of writing this journal is to analyze the legal position of the directors who act as personal guarantees in the event of bankruptcy. This journal is a normative juridical research, with a statute approach and a case approach. This journal analyzes that it has not been specifically regulated in the Indonesian Bankruptcy Law, the position of the Personal Guarantor or individual guarantor in the event of bankruptcy. This journal also finds that Personal Guarantor can turn into a debtor and be bankrupt when the guarantee agreement states explicitly that the guarantor has given up his privileges while the main debtor cannot fulfill his agreement which can make the guarantor a debtor and can be filed for bankruptcy against him. In a Limited Company, the Board of Directors as a personnel officer who has been declared to have lost the right to dominate and take care of his wealth which is included in bankruptcy property and it can be confiscated if it has been decided by the commercial Court.